Identification of fish in the Rasau and Sempaya River in Pelalawan Village, Riau Province - Irna ramadhani; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTRasau and Selempaya riveris one of the Pelalawan village. However, the information about these kinds of fish in the area is still limited. To understand the types of fish present in the rasau and selempaya river, a study has been conducted in March 2019. Catching is carried every day for two weeks until there is no longer found a new species of fish. Fish catching was done by using line fishing’s, “langgi” and “togun”. Fish sampled were then identified based on Kottelat et al. (1993) and Saanin (1968). Results shown that the caught fish consistsof 3 orders, 11 families, 13 genera and 21 species. The condition of the water quality at rasau and selempaya river shows that temperature of 28oC-31oC, brightness of 30-76.5 cm, depth 1,6-4 m, flow velocity 0.010-0.017 m / sec, pH of 5-5.5, dissolved oxygenof 3,7-4,4 mg/L and carbondioxide 16-17 mg/L. Keywords: Identification, Rasau River, Selempaya River